Expansile Lytic Lesions of Rib: Two Rare Case Reports - Yadav, Priyanka; Singh, Lokesh; Debi, Uma; Bhatia, Vikas; Sinha, Anindita; Sandhu, MS (Archives of Clinical and Medical Case Reports, 2020)
Of all primary bony tumors, chest wall is involved in only 5 – 8 % cases. Chondroblastoma and aneurysmal bone cyst (ABC) rarely occur in chest wall. Here, we would be presenting two such rare cases .One, a 26 year old male presenting with history of chest pain for 1 ½ year and other a 37 year old male with the chief complaint of pain in left shoulder for 3 years. X –ray, CT scan and MRI was done followed by guided FNAC and diagnosis of aneurysmal bone cyst in case1 and chondroblastoma in case 2 was made.